PENGARUH GOOD CORPORATE GOVERNANCE, RETURN ON ASSET, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP TAX AVOIDANCE (Students' Journal of Accounting and Banking, 2015)
This study is a study that examines the effect of good corporate governance, Return on asset, size and leverage against tax avoidance to companies that enrolled in corporate governance perception index (cgpi) on 2010-2013 a period of years. Data used in thid research is taken from secondary data who is enrolled in corporate governance perception index (cgpi) on 2010-2013 aperiode of the year. A method of the sanple collection by the use of sampling purposive with a periode of research 2010-2013. The numbr of samples gathered 55 companies. An analysis of the data used that is linear regression worship of idols classical test the assumption consisting of normality test, multikolinearitas test, autokorelasi test, heteroskedastisitas test, koefesion test determination, the f and statistical test t. The research result indicates that and good corporate governance is not affect signifikn against tax avoidance, return on asset no significant posotivr effect on tax avoidance, the size of the influential positif significantly to tax avoidance  and leverage significant negative effects of tax avoidance.Keywords: Tax Avoidance, Good Corporate Governance, Return On Asset, Size and Leverage